KEWENANGAN POLISI REPUBLIK INDONESIA DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI SAMARINDA - Dewi Ratnasari (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Mental crisis , including honesty and also one Corruption . When Corruption was performed in congregation in a large scale and allowed to drag on , as was the case during this, the state that directly suffer the consequences , which encroached on the financial and economic continuously not managed according to the principles of true economy. Many efforts were made to strengthen the eradication of corruption in a way to create, improve and revise the regulations regarding the Corruption Eradication so as if there is no gap for the release of criminals from the law. But the success of an Act to prosecute perpetrators Crime is also very dependent on law enforcement officers as executors. Barriers Investigation conducted the investigation of corruption, absence of legislation governing the permission / approval to be filed / submitted by the Prosecutor prior to the Officer / Agency action specified in the call / examination of witnesses / suspects particular, a search or seizure of evidence, as well as in the calculation of state assets. The existence atauran minister / head of the institution that require employees / staff must be with permission of leadership without first or should the warrant prior leadership duties when called upon by the Attorney to testify . Then for each submission also requires documents / letters should be with prior permission of the head of state on the grounds of confidentiality considerations